New Proposals on Portuguese Vegetation - Pinto-Gomes, Carlos; Paiva-Ferreira, Rodrigo; Meireles, Catarina (Lazaroa, 2007)
As a consequence of the geobotanical studies that have been developed in central and southern areas of the Iberian Peninsula, five new phytosociological associations are proposed. Three of them represent perennial, mesophytic grasslands of Stipo giganteae-Agrostietea castellanae (Euphorbio transtaganae-Celticetum giganteae, Avenulo hackelii-Celticetum sterilis and Avenulo occidentalis-Celticetum giganteae). The other two are Mediterranean potential natural forest of Querco-Fagetea and Quercetea ilicis (Arisaro vulgare-Quercetum pyrenaicae and Teucrio salviastri-Quercetum suberis, respectively). For each proposed unit, besides its syntaxonomical fitting, we present its ecological diagnosis and the serial and catenal context, as well as its patrimonial value.